HIGH PERFORMANCE LIQUID CHROMATOGRAPHY FOR DETERMINATION OF METOPROLOL ENANTIOMERS IN PHARMACEUTICAL FORMULATIONS - Magiera, Sylwia; Adolf, PhD Weronika; Baranowska, Prof. Irena (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A novel high performance liquid chromatography with fluorescence detector (HPLC-FL) method for determination of metoprolol enantiomers in a pharmaceutical formulation was developed and validated. This study investigated the ultrasound-assisted extraction (UAE) of metoprolol from commercial tablets using methanol as extraction solvent. The separation of enantiomers was successfully carried out with a CHIRALCEL OD-RH column, under isocratic elution mode using 0.05% trifluoroacetic acid and 0.05% diethylamine in water and acetonitrile (80:20, v/v). The chromatographic method was validated in terms of precision, accuracy, detection and quantification limits, linearity and recovery. Calibration curves were linear in the investigated range with correlation coefficient better than 0.9931 while the limit of quantifications was 0.19 Âµg mL-1 for S(â€“)-MET and 0.23 Âµg mL-1 for R(+)-MET. The mean recovery of S(â€“)-MET and R(+)-MET from tablets were found to be 78.8% and 92.1%, respectively. This method for the direct determination and quantification of metoprolol enantiomers in pharmaceutical formulations is suitable for routine analyses in quality control laboratories and was applied to evaluate for the first time, the presence and the quantities of cited analytes in commercially available formulation. Â